APPLICATION OF COMMUNICATION INFRASTRUCTURE THEORY IN EXPLORING THE VOICE OF COMMUNITY IN CONFLICT-PRONE AREAS - Isnaini, Muhamad (Sosiohumaniora, 2024)
This research is motivated by conflicts in urban areas, which are escalating in frequency. Johar Baru District was selected due to the prevalence of inter-group conflicts, specifically in the form of brawls, which have become a daily occurrence in the area. The prevalence of this kind of conflict traumatizes the residents left behind in the area. Consequently, there is a pressing need to explore the voices of the community in conflict-prone areas that need to be explored. Communication infrastructure theory was chosen to support the analysis because this theory was developed to articulate problems in urban areas. The research method chosen is a case study. The research results show that the community expressed three essential things related to conflict: the dangers of drugs, peace, and providing employment opportunities. This research also shows that Communication Infrastructure Theory (CIT) is reliable for mapping conflict in urban areas as well as capturing the voices of communities that have been marginalized in conflict-prone areas.